Thermo-Responsive Microfibrillar Graft Copolymer Based on Carboxymethylagarose and N-Isopropylacrylamide - Ortiz-Nunez, J; Zapata-Ramirez, P (Elsevier Ltd, 2020)
Carboxymethylation of agarose with ClCH2COOH in 2-propanol, formamide or dimethyl sulfoxide were evaluated in order to obtain water soluble derivatives. Higher yield (86%) and degree of substitution of carboxymethylation in primary alcoholic groups (0.70) were obtained using dimethyl sulfoxide. Carboxymethylagarose-g-PNIPAAm copolymers were synthesized by free radical graft copolymerization using Ce4+ and S2O8 2−/TEMED as initiators via conventional or microwave-assisted methods. Carboxymethyl derivatives and graft copolymers were characterized by FT-IR and NMR spectroscopies, elemental analysis, TGA and DSC and morphology analysis by SEM and AFM. High nitrogen content (9.7%) was found with Ce4+ by conventional method and the obtained analysis allowed to confirm the NIPAAm grafting on the carboxymethylagarose chain. Thermoresponsive materials have a low critical solution temperature between 32 and 34 °C. Thermal stability increased ca. 60% with PNIPAAm grafting. Surface analysis of copolymers reveals a microfibrillar type morphology with diameter of 4–6 μm. Synthesized glycoconjugates could find applications in bioactive compounds transport in biological systems. © 2019